2013
DOI: 10.1111/ajr.12035
|View full text |Cite
|
Sign up to set email alerts
|

Splenic injury admitted to a rural Level 3 trauma centre: A 10‐year audit

Abstract: Although splenic injury is uncommon in the Wimmera region, improved trauma triaging is required, with early transfer of unstable patients and high-energy trauma mechanisms. A lower threshold for computed tomography scanning is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…CT is superior to ultrasonography, due to the fact that it is a less operatordependent method, offering higher sensitivity for the detection of solid organ injuries. In the study by Hoskins et al (8), which evaluated patients who sustained splenic injury, the delay in performing CT was associated with a delay in surgery and the occurrence of major postoperative complications. The same study also concluded that among patients having a higher risk for developing splenic injury, those who sustained high-energy trauma and who exhibited hemodynamic instability should be considered high-risk patients and should undergo CT as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…CT is superior to ultrasonography, due to the fact that it is a less operatordependent method, offering higher sensitivity for the detection of solid organ injuries. In the study by Hoskins et al (8), which evaluated patients who sustained splenic injury, the delay in performing CT was associated with a delay in surgery and the occurrence of major postoperative complications. The same study also concluded that among patients having a higher risk for developing splenic injury, those who sustained high-energy trauma and who exhibited hemodynamic instability should be considered high-risk patients and should undergo CT as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lower-level trauma centers with limited resources must expeditiously decide who can be immediately transferred to a higher level of care for SAE and who can be safely admitted for either surgery (exploratory laparotomy and splenectomy) or observation. Although there are a proliferation of studies examining the triage of splenic injuries [3,[6][7][8][9][10][11][12][13][14][15], there are a paucity of studies on management of patients with blunt splenic injuries in remote settings and of the few that exist, most report very small numbers and are not current [16,17]. There continues to be great variability in the processes of care for splenic injury patients, with sparse data reported across Level III or IV trauma centers.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is published about SAE in transferred trauma patients. A search in PubMed with the terms “splenic AND injury AND transfer” yielded only one paper describing six cases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%